Adiksi Internet pada Masa Dewasa Awal - Mawardah, Mutia (Jurnal Ilmiah Psyche, 2019)
This study aims to determine internet addiction in early adulthood. What aspects and factors influence addiction in early adulthood. Addiction shows psychological and physical characteristics. Physical dependence occurs when the body of an individual experiences dependence on certain substances and experiences â€œsakauâ€ symptoms when removing their consumption. This study uses qualitative research design and uses phenomenological research to be able to find out addiction in early adulthood using a questionnaire from IADQ (Internet Addiction Diagnostic Questionnaire), which is a measure developed for diagnoses that conceptualizes the eight criteria for internet addiction disorders. In this study, researchers used five sources of research subjects. Data collection in this study was carried out using interview, observation, and documentation techniques on five subjects that have addiction to the subject's internet. The results of this study found that there is a neuropsychological chain model, namely there are six main concepts in relation to internet addiction, namely cognitive drive, euphoric experience, tolerance, abstinence reactions, passive coping and avalanche effects, and the results of research find there are factors that support internet addiction in middle adulthood, namely factors of interaction between internet users, factors available for internet facilities, factors of lack of supervision, factors of lack of motivation reduce internet usage in users and factors of users less able to control behavior in using the internet